Characteristics of teachers that influence the reduction of normalized inequality, view of Mexican high school students - Terrazas-Medina, Tamara Isabel (2025)
This study was carried out in five high schools in northeastern Mexico, where 79.5% of the students were from the “low” marginalization sector and the schools of origin were not among the best in the region. Objective: To know the characteristics of teachers that influence the reduction of Normalized Inequality in high schools in northeastern Mexico. Qualitative, descriptive and transversal research. 91 students from different populations in the northeast participated. Collection instrument: open qualitative questionnaire, data collected in forms, analysis was through triangulation. The results indicated that teachers worked in the classroom so that educational results were the best. It was concluded that the particularities of these teachers were referred to educational work with values, principles, virtues, basic pedagogical skills and advanced pedagogical skills; In addition, the importance of the teaching pro-cedure that encouraged, promoted and promoted the learning of knowledge with quality was revealed.